Sudden death associated with delayed cardiac rupture: case report and literature review - Tinzin, Lopsong; Gao, Xuefei; Li, Hui; Zhao, Shuquan (Frontiers in Cardiovascular Medicine, 2024)
Cardiac injury plays a critical role in the process of thoracic trauma-related fatal outcomes. Historically, most patients who suffer a cardiac rupture typically die at the scene of occurrence or in the hospital, despite prompt medical intervention. Delayed cardiac rupture, although rare, may occur days after the initial injury and cause sudden unexpected death. Herein, we present the clinical details of a young man who suffered a chest stab injury and recovered well initially, but died days later due to delayed cardiac rupture. The forensic autopsy confirmed delayed cardiac rupture as the cause of death. We also reviewed previous similar reports to provide suggestions in such rare cases in clinical and forensic practice.